An industrial quality control study on Nation Paper Products and Printing Corporation - Hofileña, John Rya.; Lim, Angelito Jr.; Magtoto, Antoni; Soriano, Erick Jo. (Diliman, Quezon City College of Engineering, 2001)
Nation Paper Products and Printing Corporation controls a market share of at least 30% of local office and school paper supplies. NAPPCO, as it is popularly known, sells an average 90 million tons of paper in the local market annually. Despite being in the industry for 50 years, quality problems exist in the company that hinder its rapid growth. These major causes of rejection addressed by the study are surface imperfections, poor cut edges and dimensional inconsistencies. Statistical Process Control and Process Capability Analysis was done to analyze these three problems. Results showed the cutting and sheeting process are in control but with unacceptable process capability. Surface imperfections refers to damages on the sheet like blemishes and discolorations. The major trigger of this problem is the inefficient materials handling system of the company. The use of conventional pallet racks would protect the raw materials during forklift operations. Poor cut edges occur when cutting blades are overused. A "change blade after 50,000 cuts" policy is introduced to address this problem. Dimensional inconsistencies occur in the cutting and sheeting process where the paper is reduced to the desired size. Through statistical process control and the introduction of control charting to monitor worker output, human errors may be reduced. Since NAPPCO is planning for an ISO certification, a study of all the process involved in producing its various products is essential. In addition, benchmarking and methods engineering engineering would be beneficial to the company.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Nation Paper Products and Printing Corporation; Paper industry; Quality control